P.3.24 Prevalence of non-fatal injuries in informal waste recyclers in landfill sites in johannesburg, south africa. (April 2019) - Naicker, Nisha; Kootbodien, Tahira; Ntlebi, Vusi; Wilson, Kerry; Made, Felix; Tlotleng, Nonhlanhla; Ndaba, Mpume; Kgalamono, Spo; Mathee, Angela
Abstract : Background: Waste recyclers at landfill sites separate, collect and sell recyclable solid waste. They do not receive Occupational Health and Saftey (OHS) training, personal protective equipment (PPE) or health support. There is limited information of the extent of adverse health outcomes experienced by waste recyclers in South Africa. The objective of this study was to assess the prevalence and possible risk factors for injuries experienced by waste recyclers. Methods: A cross sectional study was conducted among waste recyclers working in two landfill sites. Interviews were conducted with 361 waste recyclers using a structured questionnaire with information on socio-demographic history, exposures and injuries experienced. Logistic regression with OR was used to determine the significant risk factors for having experienced an injury in the last 6 months. Results: The average age was 33.7 years, range of 18–81 year. The majority were male (73.4%) and had completed secondary school education (77.8%). The average income earned was $119 per month and 51% lived in informal dwellings. Exposures included rodents (91%), lifting heavy object (87%), dogs (78%), chemicals (66%), needles (43 .%), falling waste (38%) and violence (20%). Although 90% of participants stated they wore some kind of PPE, this was not always suitable for the work conducted. 33% experienced an injury. The commonest injuries were bitten by rats (90%), falls on site (46.7%), muscular pain (29%), dog attacks (21%), violence from other waste pickers (20%) and needle stick injuries (20%). Logistic regression results showed that being male (crude OR 2.94, 95% CI- 1.399–6.195) and age <34 years (crude OR=2.69, 95% CI 4.145–4.988) were significant risk factors for injuries. Conclusion: There is a high prevalence of injuries experienced by waste recyclers at landfill sites. OHS awareness and use of appropriate PPE should be provided to waste recyclers in order to prevent occupationally related injuries.